Identificación de ácaros causantes de sarna en caninos con dermatitis clínica en la veterinaria Pet Shop de la ciudad de Quevedo. - Almeida González, Tito Daniel (2024)
This research evaluated the presence of mange-causing mites in canines with clinical dermatitis at the Pet Shop Veterinary Clinic in Quevedo, Ecuador. Fifty dogs were examined using skin scraping, acetate tape impression, and smear techniques. Results revealed a 6% incidence of Demodex canis, with no cases of Sarcoptes scabiei or Cheyletiella spp. Skin scraping proved to be the most effective method for mite detection. No statistically significant associations were found between the presence of mites and factors such as breed, sex, or age, although a trend towards higher prevalence in adult and male dogs was observed. Bulldog and mixed breeds showed the highest incidence (14.3% each). A survey of owners revealed that 70% noticed reddened or inflamed skin, 60% observed an increase in affected areas, and 90% reported their dogs had contact with other canines outside the home. These data highlight the importance of educating owners about early detection of dermatological problems. The study underscores the effectiveness of skin scraping in mite diagnosis and the need to implement control and prevention programs. The low incidence of mites, compared to previous studies in Ecuador, suggests possible differences in environmental conditions or effectiveness of control measures in Quevedo. Additional research is recommended to better understand the dynamics of mite transmission in the region.